Evaluation of Learning Program in Improving Teacher Competence of Madrasah Tsanawiyah in Bengkulu - Nadrah Nadrah; Puji Rahayu (UIN Fatmawati Sukarno Bengkulu, 2024)
Abstract: Teacher competence in learning still got difficulties in terms of pedagogical competence, personality competence, social competence and professional competence. The aim of this research was to evaluate and analyze learning programs in improving teacher competency. This research used the Context, Input, Process, and Product (CIPP) method with primary and secondary data sources. The research results showed that (1) in context, teacher competency is generally quite good, but there were still teachers who could not display their professionalism; (2) learning program input, 20% was not appropriate, 20% teacher competency was not able to make plans. The learning implementation level of 40% had not been implemented according to the program. The learning outcomes evaluation level of 40% was not in accordance with the plans that had been prepared, the budget and facilities were generally quite available, but they were still quite limited; (3) the process of implementing learning in general was quite good, but there were still teachers whose punctuality was still weak, the application of learning methods, evaluation and monitoring, human resource development, teacher recruitment, and services and innovative creative behavior were still found to be not optimal and there were still obstacles ; and (4) The products or achievements of the learning program were generally quite good, but there were still teachers who had not been able to demonstrate their professionalism. Therefore, it can be concluded that the results of the learning program evaluation in general revealed that teacher competence was quite good, but there were some teachers whose competence was not optimal. Thus, teachers were advised to improve teacher competency and improve evaluation of teacher learning programs in schools.Keywords: Evaluation of Learning Program, Teacher Competence, Madrasah Tsanawiyah Abstrak: Abstrak: Kompetensi guru dalam pembelajaran masih mengalami kesulitan baik dari segi kompetensi pedagogik, kompetensi kepribadian, kompetensi sosial dan kompetensi professional. Tujuan penelitian ini untuk mengevaluasi dan menganalisis program pembelajaran dalam meningkatkan kompetensi guru. Penelitian ini menggunakan metode Context, Input, Process, and Product (CIPP) dengan sumber data primer maupun data sekunder. Hasil penelitian menunjukkan bahwa (1) context. Kompetensi guru secara umum cukup baik, namun masih ada guru yang belum dapat menampilkan keprofesionalannya; (2) input program pembelajaran, 20% belum sesuai. Kompetensi guru 20% belum mampu membuat rencana. Tingkat pelaksanaan pembelajaran 40% belum dilaksanakan sesuai program. Tingkat evaluasi hasil pembelajaran 40% tidak sesuai rencana yang telah disusun, anggaran, dan fasilitas secara umum cukup tersedia, namun masih cukup terbatas; (3) proses pelaksanaan pembelajaran secara umum cukup baik, namun masih ada guru masih lemah ketepatan waktu, penerapan metode pembelajaran, evaluasi dan monitoring, pengembangan sumberdaya manusia, rekrutmen tenaga guru, dan pelayanan serta perilaku kreatif inovatif masih ditemukan belum maksimal dan masih terdapat hambatan; dan (4) Produk atau capaian dari program pembelajaran secara umum cukup baik, namun masih ada guru yang belum dapat menunjukkan profesionalitasnya. Sehingga dapat dsimpulkan bahwa hasil evaluasi program pembelajaran secara umum kompetensi guru cukup baik, namun terdapat sebagian guru kompetensinya belum optimal. Dengan demikian guru disarankan untuk meningkatkan kompetensi guru dan meningkatkan evaluasi program pembelajaran guru di sekolah.Kata Kunci: Evaluasi Program Pembelajaran, Kompetensi Guru, Madrasah Tsanawiyah